Research protocol of a multifaceted, comparative mixed-method study: Young people transitioning from out-of-home care in Norway and Australia - Interrelationships between policies, pathways, and outcomes. - Veronika Paulsen; Christian Wendelborg; Stian H Thoresen; Lauren Parsons; Donna Chung; Melissa O'Donell; Regine Ringdal; Reinie Cordier (PLoS ONE)
Introduction Young people who have been in the care of child welfare systems face myriad challenges as they transition into adulthood, resulting in poor long-term outcomes. The overwhelming international trend shows that compared with their peers who have not been in care, care leavers are more likely to experience unstable living conditions, low engagement in employment, financial instability, low levels of educational attainment, poor physical and mental health, and involvement in criminal justice systems. Child welfare policies to support young people as they transition to independence are implemented differently in different countries, leading to different outcomes. Methods and analysis We will compare administrative data from Norway and Australia to objectively quantify and compare, at a population level, associations between service use pathways and young people's outcomes as they transition from out-of-home care within different policy contexts. In addition, the study includes in-depth interviews with young care-experienced people, their carers, and service providers. The mixed-methods study will make cross-country comparisons of the lived experiences of young people, their carers, and service provision practices that act as barriers and facilitators to positive long-term outcomes within Norway and Australia. The combined findings from the population-level data and an in-depth understanding of their lived experiences will identify a best practice model to facilitate better outcomes. A critical policy analysis and synthesis will be conducted alongside these studies to highlight the influence of policy on service provision practices, young people's pathways, and outcomes. Discussion To date, there have been no international comparisons at a population level to determine how various policy contexts influence outcomes for care leavers, thus not allowing a granular explanation for why young people continue to experience poor outcomes. This project will develop a nuanced and dynamic understanding of how different policies and practices produce pathways that either promote or constrain positive outcomes in adulthood. The comparisons across Norway and Australia will generate unique knowledge by enhancing our understanding of internal and external child welfare services, country-specific, and individual characteristics in policies and practices enhancing outcomes for young people transitioning from out-of-home care.